Mixed convection due to rotating cylinder in an internally heated and flexible walled cavity filled with SiO2-water nanofluids: Effect of nanoparticle shape - Selimefendigil, Fatih; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Pergamon-Elsevier Science Ltd, 2016)
In this study, numerical investigation of mixed convection in a square cavity filled with SiO2 nanofluid and volumetric heat generation is performed under the effect of an inner rotating cylinder and a flexible side wall. The top wall of the cavity is kept at constant cold temperature while the bottom wall is at hot temperature and the other walls of the cavity and the cylinder surface are assumed to be adiabatic. The finite element method is utilized to solve the governing equations. The Arbitrary Lagrangian-Eulerian method is used to describe the fluid motion with the flexible wall of the cavity in the fluid-structure interaction model. The effects of external Rayleigh number (between 10(3) and 5 x 10(6)), internal Rayleigh number (between 10(4) and 10(6)), Young's modulus of the flexible wall (between 5 x 10(2) and 10(6)), angular rotational speed of the cylinder (between - 2000 and 2000) and nano particle volume fraction (between 0 and 0.03) on the fluid flow and heat transfer are numerically studied for different solid nanoparticle shapes (spherical, cylindrical, brick and blade). It is observed that as the value of external Rayleigh number increases, internal Rayleigh number and elastic modulus of the flexible wall decrease, the local and averaged heat transfer enhances. The averaged heat transfer enhances with cylinder rotation in both directions for all nanoparticle types. Among all nanoparticle shapes, cylindrical ones show the best performance and spherical ones show the worst performance for heat transfer enhancement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Nanofluid shape; Rotating cylinder; Finite element method; Fluid-structure interaction